Pesticide safety practice and its public health risk in African regions: systematic review and meta-analysis - Dechasa Adare Mengistu; Abraham Geremew; Roba Argaw Tessema (BMC, 2024)
Abstract Background Although pesticides play an integral role in food security and preventing public health from vector-borne diseases, inappropriate handling and continual use of restricted organochlorine pesticides pose short- and long-term adverse effects and become public health concerns in the African region. This study aimed to determine the combined level of protective equipment use, management of empty pesticide containers, and leftover pesticide residues in the African region. Methods The preferred reporting items for systematic reviews and the meta-analysis protocol were used to carry out this study. The Scopus, PubMed, Web of Science, Google Scholar, DOAJ, and National Repository databases were searched for articles published between November 12, 2023, and January 2, 2024. The meta-analysis data were visualized using a forest plot. A random-effects model was applied when heterogeneity existed in pooled studies. Subgroup analysis of the data was performed based on the location where the study was conducted and the publication year. Meta-regression and sensitivity analysis were performed to evaluate the robustness of the pooled prevalence of studies. Publication bias was assessed using a funnel plot. The authors used the Joanna Briggs Institute Critical Assessment tool to determine the quality of the studies. Results In this review, 2174 articles were identified from the included electronic databases, 24 of which were included in the present study. The study revealed that the combined mean prevalence of wearing a mask, glove, boot/safety shoes, overall wear, and head cover accounted for 18% (95% CI: 11.9 to 26.1%, p < 0.001), 18% (95% CI: 11.7 to 26.9%, p < 0.001), 23% (95% CI: 15.7 to 33.3%, p < 0.001), 26% (95% CI: 16.2 to 38.7%, p < 0.001), and 14% (95% CI: 8.90 to 22.0%, p < 0.001), respectively. The prevalence of pesticides stored in the living room and pesticide containers used for different purposes was 51% and 26%, respectively. Conclusions Poor pesticide safety practices were identified. A substantial proportion of the respondents reported storing pesticide residues in their living rooms, and the reuse of pesticide empty containers. Regional institutions should lead the designing of safety strategies to reduce the public health risks of pesticide exposure.